Health care utilisation amongst older adults with sensory and cognitive impairments in Europe - David G. Lugo-Palacios; Brenda Gannon (Health Economics Review, 2017)
Worldwide, the high prevalence of multiple chronic conditions amongst older population has led to increased utilisation of health care and rising associated costs, becoming a major public health concern. Hearing, vision and cognitive disorders are common chronic conditions amongst older Europeans and recent studies have documented its high co-occurrence. While it has been shown separately that suffering either mental disorders or sensory (hearing and vision) impairments is associated with higher health care utilisation, the association between health care utilisation and the interaction of these conditions has received little attention in the literature. Therefore, using four waves of the Survey of Health, Ageing and Retirement in Europe (SHARE), this study applies the correlated random effects method to the negative binomial and finite mixture models to analyse the extent to which the interaction of cognitive and sensory impairments is associated with health care use. We found that individuals with cognitive impairment tend to have more hospitalisations. The finite mixture approach indicates a positive association between sensory impairment and the number of hospitalisations amongst low users of health care. Additionally, our findings suggest a positive association between suffering both impairments at the same time and the number of doctor and GP visits.
Keywords: 330; Ageing; cognitive mpairment; Sensory impairment; Health care utilisation; Correlated random effects; SHARE